As The World Welcomes Its Seven Billionth Human: Reflections On Population, Law, And The Environment - Hardaway, Robert (Journal of Sustainable Development Law and Policy, 2025)
Twenty years ago, Praeger Publications of Westport Connecticut published this author’s book “Population, Law and the Environment”,1 in which the case was made for identifying human population expansion as the key environmental issue of our times. This case rested in large part on linking together cultural and legal issues, which theretofore had not always been considered to be related to environmental protection, such as abortion, the rights of women, contraception, immigration, family planning, and policies of economic growth. There have been considerable developments in these areas which have spurred this author to update his book, this time in the form of this article which both condenses the content of his previously published book where apposite (including passages which are incorporated verbatim from his previous work), and updates the most recent data supporting its original premise. The case is renewed herein for linking those areas which continue to be widely ignored or rejected as relevant to environmentalism, while at the same time urging that the environmental movement and the law that supports it expand its current narrow focus on the “A” and “T” factors of Holdren’s2 brilliantly conceived equation (I=PAT), and recognize the more critical “P” component, which in turn is a reflection of how both domestic and international law promulgates and enforces law in the areas identified in this article. The name that the author has adopted for this proposed change of focus is “Environmental Malthusianism.”